Customization, Parameterization, and Scaling of the iSAT: An ICT based Agro Advisory platform for location-specific Informed Decision-Making - Kumar, Kishore G.; Kumar, Shalander; Rao, K.P.C.; Patil, Mukund; Jat, M.L. (International Food Policy Research Institute, 2024)
Following the successful demonstration of the iSAT system's ability to generate data-driven, science-based weather advisories, efforts were undertaken to scale the system and improve its capabilities. The focus was on four key areas; expanded crop coverage to cover a wider range of crops, flexible information access to accommodate local information and user preferences, targeted and timely advisories tailored to specific crop growth stages and delivered at the right time and multilingual and multi-format advisories (SMS, mobile app, WhatsApp, website) to reach a diverse audience. To achieve these goals, the ISAT system was modified in several ways. Location-specific information was incorporated through lookup tables, mobile apps, and direct input, the decision-making process was refined to generate advisories that align with farmers' specific needs, advisories were produced in two formats: SMS-friendly and detailed versions for mobile apps, WhatsApp, and websites and options were added to translate advisories into local languages. The challenges and limitations in realising the full potential of context-specific advisories include availability of reliable and consistent data, tailoring advisories to specific conditions that requires further refinement and adaptation, effective delivery through various mobile devices and platforms, government policies on bulk SMS and data privacy, language barriers requiring translation and localization for reaching a wider audience and user awareness and capacity to utilize them information effectively. By addressing these challenges, the ISAT system can continue to evolve and provide even more valuable and impactful services to farmers and agricultural stakeholders.